CP violation in the 3 jet and 4 jet decays of the Z boson at gigaZ - Nachtmann, Otto; Schwanenberger, Christian (The European physical journal. C, Particles and fields, 2003)
.We review CP-violating effects in Z→3Z→3Z → 3 jet and Z→Z→Z → 4 jet decays, assuming the presence of CP-violating effective Zbb¯GZbb¯GZ b \bar{b} G and Zbb¯GGZbb¯GGZ b \bar{b} G G couplings. Longitudinal beam polarization is included in the studies. We propose a direct search for such CP-violating couplings by using various CP-odd observables. The data of a future linear collider running at the Z-resonance in the so-called GigaZ option should give significant information on the couplings. Finally we show that stringent bounds on the mass of excited b quarks can be derived if appropriate couplings are of a size characteristic of a strong interaction.
Gesehen am 07.03.2018